ANALISIS NILAI TAMBAH DAN STRATEGI PENGEMBANGAN PRODUK MIE UBI JALAR UNGU PADA AGROINDUSTRI UD. NULA ABADI - Rosidatul Qomariyah; Ebban Bagus Kuntadi (UPT Penerbitan Universitas Jember, 2018)
The production of purple sweet potato plants in East Java is quite abundant however lack of optimization so it has a low selling price of around Rp. 3000 - Rp. 4000 / Kg. In order for the selling value of purple sweet potato to increase the way it does is by processing purple sweet potato into a secondary product. Agroindustry is a diversification of agricultural production that provides benefits in agricultural development . Agroindustry that does processing activities from purple sweet potato is agroindustry UD. Nula Abadi in Bondowoso District which processes sweet potatoes into flour. Then flour is processed into processed products, one of which is purple sweet potato noodles. Purple sweet potato flour has better content and also interesting results the distinctive taste and color of purple sweet potato in making noodles. Products from agroindusty are new innovations. Based on the phenomenon of researchers wanting to find out whether sweet potato noodles provide added value and agroindustry development strategies for purple sweet potato noodle products , research is needed regarding the value added analysis and development strategies of purple sweet potato noodles . The method of determining the sample used is purposive sampling based on the data sources needed with consideration of peoplewho are considered to understand the research . Methods of data collection using interview techniques, observation and literature. The analytical method used is the Hayami method to determine the value added analysis and to use the SWOT analysis to determine the development strategy of purple sweet potato noodles. The results of this study indicate that (1) The added value of purple sweet potato noodles provides moderate added value. The added value obtained is Rp. 51,020 / Kg with a value added ratio of 57.98%. (2). The development strategy of purple sweet potato noodles are in a position that is stronger Area White-chance. So that, prospective and potential opportunities for the construction and development of agroindustry -UD. Nula Abadi in the future.